DeepTCR is a deep learning framework for revealing sequence concepts within T-cell repertoires - John-William Sidhom (Nature Portfolio, 2021)
The advent of high-throughput T-cell receptor sequencing has allowed for the rapid and thorough characterization of the adaptive immune response. Here the authors show how deep learning can reveal both descriptive and predictive sequence concepts within the immune repertoire.